Training and Assistance for Farmer Group the Community of Relationship in Distributing Leading Agricultural Products Based on E-Commerce - Sitohang, Ance Marintan D; Sianipar, Aryanti S.; Zendrato, Niskarto; Eqlima (Talenta Publisher, 2023)
Humbang Hasundutan (Humbahas) is a district in the province of North Sumatra, which has potential natural resources, especially in the agricultural sector. Humbahas is used as a pilot area for special horticulture agricultural corporations in North Sumatra. The development of the Humbahas area aims to improve food security and farmer capacity. The devotional activities aim to provide assistance and training to the Sira-Sira village farming community group in hopes of expanding the marketing area that will have an impact on increasing farmers' income. The problem faced by partners is the limited ability and management of partner business management, especially in marketing superior agricultural products to a wider market, especially in marketing agricultural products online, in this case using the internet (e-commerce) network. This activity begins with delivering material related to e-commerce, then providing training to partners about online marketing techniques and business assistance. Through this training, partners are expected to have the ability to access the online marketplace (e-commerce). The results of this activity indicate that the farmer groups who attended the activity were very enthusiastic about participating in the training because they felt it was helpful to use online media as a means of marketing their superior agricultural products.